(untitled) (Bangladesh Journal of Microbiology, 2016)
Being a popular ready-to-eat food among all age groups, ice creams warrant the maintenance of sound microbiological quality for the sake of public health safety. Present study investigated the microbiological quality of the commonly consumed ice creams available within the retail shops in Dhaka city, Bangladesh. Five ice creams from each comprising 3 types of samples (soft, hard & flavored) of 7 most popular brands (a total of 90 samples) were collected and assessed for the presence of contaminating bacteria through conventional microbiological and biochemical identification methods. Total viable bacterial load was estimated within a range of 4.9 × 103 to 7.9 × 105 cfu/ ml. Brand A ice cream samples were noticed to harbor the least amount of microorganisms. On the other hand 65% of samples belonging to brands B and C were found to be contaminated with Shigella spp. while 30% of samples of brand B and C and 60% of brand E were contaminated with L. monocytogenes. While some were found to be microbiologically sound, most of the ice cream samples studied were found to be contaminated with microorganisms. Maintenance of appropriate hygienic condition during manufacturing and storage of ice cream products are thus recommended to ensure the consumer health safety. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 45-48